PERAN WTO DALAM MENYELESAIKAN SENGKETA PRICE RANGE SYSTEM ANTARA PERU DAN GUATEMALA TAHUN 2013 - Hikmawan, Emil; Aulia, Jamal (Dauliyah Journal of Islamic and International Affairs, 2022)
The World Trade Organization (WTO) is an international organization that facilitates international cooperation in the field of economy and trade. The position of the WTO as an international regime to date certainly has an important influence in the context of a country's national economic progress. In addition, the World Trade Organization has a function to resolve trade disputes experienced by its member states. One of the disputes faced was Peru's price range system on agricultural products that were considered detrimental to Guatemala in the two countries' free trade agreements. This is evidenced by the violation of Article 4.2 by Peru, namely the determination of additional import costs is not allowed in an agreement and is not an ordinary customs duty. Based on the above issues, the authors try to see how the WTO facilitates the implementation of negotiations between the two sides based on the concept of dispute settlement mechanism. Later in obtaining the data source, the author browses news, international trade documents, WTO norms and official statements relating to the topic of this research online.Â  The article found that the WTO established a panel as a mediator to resolve the trade dispute and asserted that Peru had violated international trade norms applicable to the WTO and this was a permanent decision to be exercised by Peru.